2019
DOI: 10.1021/acs.chemrestox.9b00206
|View full text |Cite
|
Sign up to set email alerts
|

Diisononyl Phthalate Differentially Affects Sirtuin Expression in the HepG2 Cell Line

Abstract: Human exposure to phthalates has received special attention due to their possible adverse human health effects. Diisononyl phthalate (DINP) is a plasticizer still widely used in many products, despite being considered an endocrine disruptor. In this study, we evaluated DINP's cytotoxicity, its effect on the levels of reactive oxygen species (ROS), and its effect on sirtuin expression in HepG2 cells. Results showed that 1 μg/mL DINP significantly downregulated Sirt1, Sirt2, Sirt3, and Sirt5 gene expression (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…Human liver cell lines derived from hepatic carcinomas such as HepG2 and Huh7 have been widely applied in toxicity test, drug screening, and physiological studies [36][37][38] . However, discrepancies exist between the cell lines and hepatocytes in the liver, making many in vitro results irreproducible in subsequent animal and clinical trials 39,40 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human liver cell lines derived from hepatic carcinomas such as HepG2 and Huh7 have been widely applied in toxicity test, drug screening, and physiological studies [36][37][38] . However, discrepancies exist between the cell lines and hepatocytes in the liver, making many in vitro results irreproducible in subsequent animal and clinical trials 39,40 .…”
Section: Resultsmentioning
confidence: 99%
“…Human liver cell lines derived from hepatic carcinomas, including HepG2 and Huh7, have been widely applied in pharmaco-toxicology, drug screening, and physiological studies due to availability. However, significant differences exist between the cell lines and hepatocytes in the liver, making the in vitro results often irreproducible in subsequent trials. , To improve the predictivity and reproducibility of cell line-based assays, the discrepancies need to be minimized. Accumulating evidence suggests that the conventional way to culture the cells in vitro can be a cause of the discrepancies. , Cells grown in a 2D monolayer in a container or on a surface cannot recapitulate the in vivo microenvironment .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Gutierrez-García et al [14] observed a low ROS induction (1.5-fold) in HepG2 cells exposed to the highly hydrophobic plasticizer di-isononyl phthalate (DiNP). Induction of antioxidant enzymes occurs as an adaptive mechanism to the increased levels of ROS.…”
Section: Toxicity Of Plasticizers As Inducers Of Oxidative Stress In ...mentioning
confidence: 89%
“…(46,55) Em concordância, estudos indicam que a exposição humana aos ftalatos desencadeia sérios problemas de saúde, que vão desde anormalidades em órgãos reprodutivos, até a interferência na ação, metabolização, produção e transporte de hormônios no organismo. (58,59) Sendo assim, estudos descrevem que alguns ftalatos, como o di-n-bultil ftalato (DNBP), (60) di-isobutil ftalato (DIBP), (61) DEHP, (62) benzilbutil ftalato (BBzP) (63) e o diisonil ftalato (DINP) (64) desencadeiam efeitos nocivos no desenvolvimento e na reprodução em humanos e outros animais. (65) Sabe-se, por exemplo, que a exposição intrauterina aos ftalatos desencadeia diversos problemas no funcionamento do sistema endócrino, causando a perturbação do desenvolvimento de estruturas dependentes de andrógenos, principalmente por inibir a biossíntese de testosterona fetal.…”
Section: Ftalatosunclassified